The rise and decline of vocational education: China's experience 1985-2005 - Zhang, Ning [Verfasser] (My University, 2009)
"As a part of the strategic planning for national economic reforms and development, the Chinese government initiated a massive education structural reform in 1985, in which senior secondary education was streamed into two tracks: general and vocational. The vocational track grew rapidly during the first 10 years but enrolments started to fall from the late 1990s and has not peaked again, despite the government's repeated efforts. This paper argues that the rise and fall of secondary vocational education is a replica of international experiences during the first half of the 20th Century. The decline of the secondary vocational education was commonly due to many factors including the impact of globalisation and changes on the labour market, expansion of higher education, and social demand on equal rights for people with different backgrounds. In addition, it is argued that the fundamental factor is the ideological view on education from different stakeholders. China is no exception." (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.4 Asien; Berufsbildungssystem; Wirtschaftssystem; Hochschulsystem; Reform; Akademisierung; China